Development and clinical evaluation of an in-house human immunodeficiency virus-1 real-time RT-PCR quantitation assay - Wee, Sue Yuen (2012)
Quantification of Human Immunodeficiency Virus (HIV-1) RNA plays a vital role in diagnosing and monitoring HIV virological behavior in patients. Currently, the HIV antiretroviral therapy aims to suppress the HIV replication to its minimal, thus quantifying HIV RNA is an indicative tool for assessing the therapeutics response. Despite its importance in HIV treatment, most patients have limited access to the viral load tests due to cost and resource constraints. Additionally, great variability among HIV genotypes and wide dynamic range of clinical HIV RNA levels has presented tough challenges for developing Polymerase Chain Reaction (PCR)-based amplification assays.